Guiding Cell Network Assembly using Shape‐Morphing Hydrogels. Issue 31 (24th June 2020) - Viola, John M.; Porter, Catherine M.; Gupta, Ananya; Alibekova, Mariia; Prahl, Louis S.; Hughes, Alex J.
Abstract: Forces and relative movement between cells and extracellular matrix (ECM) are crucial to the self‐organization of tissues during development. However, the spatial range over which these dynamics can be controlled in engineering approaches is limited, impeding progress toward the construction of large, structurally mature tissues. Herein, shape‐morphing materials called "kinomorphs" that rationally control the shape and size of multicellular networks are described. Kinomorphs are sheets of ECM that change their shape, size, and density depending on patterns of cell contractility within them. It is shown that these changes can manipulate structure‐forming behaviors of epithelial cells in many spatial locations at once. Kinomorphs are built using a new photolithographic technology to pattern single cells into ECM sheets that are >10× larger than previously described. These patterns are designed to partially mimic the branch geometry of the embryonic kidney epithelial network. Origami‐inspired simulations are then used to predict changes in kinomorph shapes. Last, kinomorph dynamics are shown to provide a centimeter‐scale program that sets specific spatial locations in which ≈50 µm‐diameter epithelial tubules form by cell coalescence and structural maturation. The kinomorphs may significantly advance organ‐scale tissue construction by extending the spatial range of cell self‐organization in emerging model systems such as organoids. Abstract : Choreographed movement of cells and extracellular matrix (ECM) is a common, yet under‐engineered tissue‐building process. Shape‐changing metamaterials ("kinomorphs") made from precisely patterned cells in ECM are introduced. These cells program strains and trigger shape‐morphing dynamics, leading to multi‐scale kidney cell network assembly and maturation as tubules. The kinomorphs advance emerging tissue model systems by directing cell assembly over centimeters.